ANTIBACTERIAL ACTIVITY AND MECHANISM OF CINNAMON ESSENTIAL OIL AND ITS APPLICATION IN MILK - H. Y. Cui; H. Zhou; L. Lin; C. T. Zhao; X. J. Zhang; Z. H. Xiao; C. Z. Li (Journal of Animal and Plant Sciences, 2016)
Essential oils present a fine antibacterial performance against a variety of bacteria. The main component of the cinnamon oil was eugenol (75.52%). In this study, the goal was to evaluate the antimicrobial activity and reveal bactericidal mechanism of cinnamon oil. Firstly, the minimum inhibitory concentration (MIC) and the minimum bactericide concentration (MBC) of cinnamon oil were tested. The results showed the lowest MIC and MBC values of 0.025% and 0.05% respectively. The cinnamon oil exhibited high antibacterial activity against several bacteria in vitro. Meanwhile, the application of cinnamon oil in milk also proved its good antibacterial properties. Subsequently, the bactericidal mechanism of cinnamon oil was investigated. The SEM images, TEM images and the loss of 260 nm-absorbing material indicated that the cinnamon oil could damage microbial cell membrane. In addition, the loss of ATP and DNA were detected, which also implied that the direct damage of cinnamon oil to microbial cell membrane was major antibacterial mechanism.
Keywords: Cinnamon Essential oil; Antibacterial Activity; Milk; antibacterial Mechanism